INTENSIFIKASI INTERPERSONAL COMMUNICATION ACCOUNT OFFICER DALAM MENINGKATKAN VOLUME NASABAH PADA LEMBAGA KEUANGAN SYARIAH - Suparwi Suparwi (Gapenas Publisher, 2021)
Competition of financial institutions is so tight, however the development of Islamic Financial Institutions the longer shows that the positive trend cann’t be separated from the role of account officers who are important marketing figures in providing information and education to the society. Banks as financial institutions that produce financial services desperately need account officers to introduce the advantages of Sharia Banks such as mudhorobah financing, salam, Istishna'and other products such as wadi'ah, ijarah, wakalah, kafalah, hawalah, rahn, as-sharf and qard. The interpersonal ability of the communication account officer is a necessity that must always be improved considering that the spearhead of banking is in the hands of the account officer. An Account Officer (AO) must be able to attract prospective customers by optimizing interpersonal communication skills with good so that customers are interested in using Sharia Bankproducts. By optimizing the interpersonal communication capabilities possessed by account officers, of course, it will be able to influence customers and create demand to for Shariah Bank products